Antioxidant and antiradical activities depend on adrenal tumor type - Choromańska, Barbara; Myśliwiec, Piotr; Kozłowski, Tomasz; Łukaszewicz, Jerzy; Vasilyevich, Harelik Petr; Dadan, Jacek; Zalewska, Anna; Maciejczyk, Mateusz (Frontiers in Endocrinology, 2022)
The aim of the study was to assess the total antioxidant/oxidant status in the plasma and urine of patients with adrenal tumors. The study group consisted of 60 patients (31 women and 29 men) with adrenal masses, classified into three subgroups: non-functional incidentaloma, pheochromocytoma and Cushing’s/Conn’s adenoma. The number of patients was set a priori based on our previous experiment (α = 0.05, test power = 0.9). Antioxidant activity (Total Antioxidant Capacity (TAC), Total Oxidant Status (TOS), Oxidative Stress Index (OSI)) and antiradical activity (Radical-Scavenging Activity Assay (DPPH), Ferric-Reducing Antioxidant Power (FRAP)) were measured using colorimetric methods. FRAP level was decreased in plasma and urine incidentaloma (p<0.0001), pheochromocytoma (p<0.0001) and Cushing’s/Conn’s adenoma (p<0.0001), while DPPH antiradical activity only in plasma of patients with adrenal masses (p<0.0001). Plasma TAC was increased in incidentaloma patients (p=0.0192), whereas in pheochromocytoma group (p=0.0343) was decreased. Plasma and urine TOS (p<0.0001) and OSI (p<0.01) were significantly higher in patients with adrenal tumors. In pheochromocytoma patients, plasma and urine TAC (p=0.001; p=0.002), as well as plasma plasma DPPH (p=0.007) and urine FRAP (p=0.017) correlated positively with normethanephrine. We are the first who showed reduced radical scavenging capacity in the plasma/urine of patients with adrenal masses. Nevertheless, plasma TAC was significantly higher in the incidentaloma group compared to controls. Therefore, plasma and urinary antioxidant and antiradical activities depend on the presence of the tumor. Lower levels of TAC, DPPH and FRAP clearly indicate a reduced ability to scavenge free radicals and thus a lack of effective protection against oxidative stress in patients with adrenal tumors. Both plasma and urine redox biomarkers can be used to assess systemic antioxidant status in adrenal tumor patients.